Aktualisasi Nilai Syukur dan Sabar dalam Kehidupan Sehari-hari: Analisis Perspektif Al-Qur’an dan Hadis - Nur Azizatul Haqiah (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2026)
The practice of gratitude and patience is crucial in modern life, which is marked by social pressures, life’s competition, and mental health issues. These two values are not merely theological in nature but also play a role in shaping an individual’s spiritual, emotional, and social balance. However, previous research has tended to address gratitude and patience in isolation rather than examining them holistically within the context of daily life. This study aims to analyze the actualization of gratitude and patience from the perspective of the Qur’an and hadith, as well as the integrative relationship between the two as a system of moral values. The study employs a qualitative approach using literature review and thematic exegesis (maudhu’i). Data were collected from the Qur’an, hadith, exegetical works, books, and scientific journals, and analyzed using content analysis techniques. The study focuses on Surah Ibrahim verse 7 regarding gratitude and Surah Al-Baqarah verse 153 regarding patience, referencing Ibn Kathir’s Tafsir as well as the thoughts of Al-Ghazali and Ibn Qayyim al-Jawziyya. The research findings indicate that gratitude is manifested through the attitude of contentment (qana’ah), social concern, and the wise utilization of blessings, while patience is reflected in emotional control, self-resilience, and the ability to cope with life’s pressures. This study found that the integration of gratitude and patience forms a framework of spiritual ethics that contributes to psychological balance, mental resilience, and social harmony in modern life. The novelty of this study lies in its integrative analysis of gratitude and patience as a single system of ethical values that is contextual to the challenges of modern life.